Irreversible perinatal imprinting of adult expression of the principal sex-dependent drug-metabolizing enzyme CYP2C11 - Das, Rajat Kumar (Federation of American Societies for Experimental Biology, 2014)
We proposed to determine whether, like other sexual dimorphisms, drug metabolism is permanently imprinted by perinatal hormones, resulting in its irreversible sex-dependent expression. We treated newborn male rats with monosodium glutamate (MSG), a total growth hormone (GH) blocker, and, using cultured hepatocytes, examined expression of adult CYP2C11, the predominant cytochrome-P450 expressed only in males, as well as the signal transduction pathway by which episodic GH solely regulates the isoform's expression. In addition, adolescent hypophysectomized (hypox) male rats served as controls in which GH was eliminated after the critical imprinting period. Whereas renaturalization of the masculine episodic GH profile restored normal male-like levels of CYP2C11, as well as CYP2C12, in hepatocytes from hypox rats, the cells derived from the MSG-treated rats were completely unresponsive. Moreover, GH exposure of hepatocytes from hypox rats resulted in normal induction, activation, nuclear translocation, and binding to the CYP2C11 promoter of the signal transducers mediating GH regulation of CYP2C11 expression, which dramatically contrasted with the complete unresponsiveness of the MSG-derived hepatocytes, also associated with hypermethylation of GH-response elements in the CYP2C11 promoter. Lastly, neonatal MSG treatment had no adverse effect on postnatal and adult testosterone levels. The results demonstrate that the sexually dimorphic expression of CYP2C11 is irreversibly imprinted shortly after birth by a hormone other than the customary testosterone, but likely by GH.—Das, R. K., Banerjee, S., Shapiro, B. H. Irreversible perinatal imprinting of adult expression of the principal sex-dependent drug-metabolizing enzyme CYP2C11.